Differential Regulation of miRNA Profiles of Human Cells Experimentally Infected by Leishmania donovani Isolated From Indian Visceral Leishmaniasis and Post-Kala-Azar Dermal Leishmaniasis - Kumar, Ashish; Vijaykumar, Saravanan; Dikhit, Manas Ranjan; Abhishek, Kumar; Mukherjee, Rimi; Sen, Abhik; Das, Pradeep; Das, Sushmita (Frontiers in Microbiology, 2020)
MicroRNAs are small ribonucleic acid that act as an important regulator of gene expression at the molecular level. However, there is no comparative data on the regulation of microRNAs (miRNAs) in visceral leishmaniasis (VL) and post-kala-azar dermal leishmaniasis (PKDL). In this current study, we compared the expression miRNA profile in host cells (GTHP), with VL strain (GVL) and PKDL strain-infected host cell (GPKDL). Normalized read count comparison between different conditions revealed that the miRNAs are indeed differentially expressed. In GPKDL with respect to GVL and GTHP, a total of 798 and 879 miRNAs were identified, out of which 349 and 518 are known miRNAs, respectively. Comparative analysis of changes in miRNA expression suggested that the involvement of differentially expressed miRNAs in various biological processes like PI3K pathway activation, cell cycle regulation, immunomodulation, apoptosis inhibition, different cytokine production, T-cell phenotypic transitions calcium regulation, and so on. A pathway enrichment study using in silico predicted gene targets of differentially expressed miRNAs showed evidence of potentially universal immune signaling pathway effects. Whereas cytokine–cytokine receptor interaction, phagocytosis, and transforming growth factor beta (TGF-β) signaling pathways were more highly enriched using targets of miRNAs upregulated in GPKDL. These findings could contribute to a better understanding of PKDL pathogenesis. Furthermore, the identified miRNAs could also be used as biomarkers in diagnosis, prognosis, and therapeutics of PKDL infection control.